Synthesis of quaternary aryl phosphonium salts: photoredox-mediated phosphine arylation - Fearnley, A.F.; An, J.; Jackson, M.; Lindovska, P.; Denton, R.M. (Royal Society of Chemistry, 2016)
We report a synthesis method for the construction of quaternary aryl phoshonium salts at ambient temperature. The regiospecific reaction invovles the coupling of phosphines with aryl radicals derived from diaryliodonium salts under photoredox conditions.